Perancangan Signage & Wayfinding untuK Perpustakaan Nasional Indonesia - Calista, Helena; Hananto, Brian Alvin; Wijaya, Ade Maradhona Shantio (Jurnal Bahasa Rupa, 2023)
Signage and wayfinding is one of the components of Environmental Graphic Design that is used to help people feel safe and comfortable when navigating, particularly for individuals in heavily crowded locations. The Indonesian Nasional Library (Perpustakaan Nasional Republik Indonesia), recognized as the world's tallest library, comprises 24 floors filled with various services and amenities that cater to the community's interests and consistently attract many visitors. Hence, signage and effective wayfinding are indispensable in accommodating users in their library activities. The framework of this design process is established based on the pyramid method by Chris Calori & David Vanden-Eynden, with additional methods by the execution of conceptual designs, mind mapping, and the formulation of keywords. The authors aspire to contribute a signage and wayfinding design proposal that optimizes usability, resolves navigation challenges, and enhances the user experience at The Indonesian National Library.